Diagnostic effectiveness of blood and cerebrospinal fluid (CSF) parameters in patients diagnosed with meningitis in the emergency department - Mustafa Uğuz; Nur Zafer Kirdağ; Berfin Çirkin Doruk (Journal of Acute Disease)
Objective: To evaluate laboratory findings that predict bacterial meningitis in emergency service and their diagnostic effectiveness. Methods: This retrospective cohort study analyzed data from patients presenting with meningitis symptoms at a referral hospital in Mersin, Turkey, between January 2019 and January 2022. Clinical findings and laboratory results, including leukocyte count, C-reactive protein (CRP), and procalcitonin levels in blood, were examined. Logistic regression, Chi square test, and receiver operating characteristics (ROC) curve analyses assessed the predictive value of these parameters. Results: A total of 199 participants were included in the study; 99 patients were diagnosed with meningitis after lumbar puncture and 100 served as controls. Patients with meningitis exhibited significantly higher leukocyte counts (median: 11 890 × 103/μL vs. 7 905 × 103/μL, P < 0.001) and CRP levels (median: 6.00 mg/dL vs. 0.95 mg/dL, P<0.001) compared to controls. Procalcitonin levels were significantly elevated in meningitis patients (median: 0.21 ng/mL vs. 0.10 ng/mL, P<0.001). Logistic regression identified albumin (OR=0.16, 95% CI=0.06-0.40), and CRP (OR=1.18, 95% CI=1.08-1.28) as independent predictors of meningitis. ROC analysis for CRP demonstrated a sensitivity of 80.6% and specificity of 70.0% at a cut-off value of 2.23 mg/dL (AUC=0.792). Conclusions: Elevated albumin levels and CRP contents in the blood were significant predictors of meningitis in emergency service. Early identification of predictive markers may aid in timely lumbar puncture and management of atypical cases.